Inter-plant hydrogen integration with regeneration placement and multi-period consideration - Walaa Mahmoud Shehata; Abeer Mahmoud Shoaib; Fatma Khalifa Gad (Egyptian Journal of Petroleum)
Inter-plant hydrogen integration (IPHI) is getting more attention in recent years, as a result of the increasing demand for hydrogen in refinery processes, such as hydrotreating and hydrocracking. In this work, IPHI with regeneration scheme is analyzed. Indirect integration scheme is adopted, where hydrogen sources from different hydrogen networks are integrated via a centralized purifier, such as pressure swing adsorption (PSA) or membrane separation. The introduced model is able to select the optimum interception unit, which minimizes the total annualized cost. Besides, multi-period consideration is included in the analysis to address the effect of changes in operating conditions of the IPHI network on total hydrogen consumption. Two case studies are presented to demonstrate the applicability and usefulness of the proposed model. Keywords: Optimization, Optimal design, Hydrogen, Regeneration, Process integration, Multi-period